2004
DOI: 10.5089/9781451859843.001
|View full text |Cite
|
Sign up to set email alerts
|

Work Absence in Europe

Abstract: This Working Paper should not be reported as representing the views of the IMF. The views expressed in this Working Paper are those of the author(s) and do not necessarily represent those of the IMF or IMF policy. Working Papers describe research in progress by the author(s) and are published to elicit comments and to further debate. Work absence is an important part of the individual decision on actual working hours. This paper focuses on sickness absence in Europe and develops a stylized model where absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
(28 reference statements)
1
20
0
Order By: Relevance
“…Sickness absence is high in Norway compared with other countries (Bonato and Lusinyan, 2004). Several measures have been proposed to reduce the number of disability and sickness benefit claimants and to reduce the length of sickness leave (OECD, 2010) and promote faster return to work after illness or injury.…”
Section: Discussionmentioning
confidence: 92%
“…Sickness absence is high in Norway compared with other countries (Bonato and Lusinyan, 2004). Several measures have been proposed to reduce the number of disability and sickness benefit claimants and to reduce the length of sickness leave (OECD, 2010) and promote faster return to work after illness or injury.…”
Section: Discussionmentioning
confidence: 92%
“…Unlike in most other countries, no benefit cap is applied. Nevertheless, as Figure 1 demonstrates, Germany is positioned in the middle region of the country ranking and some cross-country comparisons even place Germany below the international average in terms of sickness absence rates (Bonato and Lusinyan, 2004). One explanation might lie in the anecdotal evidence that claims Germans have a strong work ethic.…”
Section: [Insert Figure 1 About Here]mentioning
confidence: 99%
“…Comparing across countries, OECD (2003b) found that benefit levels and coverage are the two most powerful predictors of sickness and disability rates (Figure 7). In a more rigorous econometric study of work absences in European countries, Bonato and Lusinyan (2004) show that the level of benefits has a large impact on the absence rate and that the elasticity is particularly big in Sweden. Their estimates suggest that cutting the benefit replacement rate by 10 percentage points would reduce absences in Sweden by around 11%.…”
Section: Beware Of Making the Sickness And Disability System Too Genementioning
confidence: 99%
“…The authors conclude that the age effect is captured within those variables. Source: OECD calculations based on the econometric results from Bonato and Lusinyan's (2004) panel data study of work absences in Europe (IMF Working Paper 04/193).…”
mentioning
confidence: 99%